2020
DOI: 10.1016/j.celrep.2020.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic-Induced Anti-tumor Immunity Attenuates Tumor Growth

Abstract: Highlights d Mucin and inulin, prebiotics, inhibit melanoma growth in syngeneic mouse models d Changes in gut microbiota taxa by these prebiotics induce anti-tumor immunity d Inulin attenuates melanoma resistance to MEKi in a mouse melanoma model d Inulin and mucin elicit distinct microbiota changes and an additive effect in select models

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 60 publications
(83 reference statements)
2
82
0
Order By: Relevance
“…Indeed, supplementation with 10% inulin in Apc Min/+ mice induced an increase of polyps and tumors size in the small intestine (46,47). However, supplementation with 15% of inulin in syngeneic wild type mice transplanted with tumors cells subcutaneously presented a slower tumor growth rate (48), and supplementation with 10% GOS in rats receiving azoxymethane and dextran sodium sulfate to induce CRC inhibited tumor growth in the colon (49). These studies did not assess the possible presence of pks + E. coli strains, which may modify responses to oligosaccharides in the tested CRC models.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, supplementation with 10% inulin in Apc Min/+ mice induced an increase of polyps and tumors size in the small intestine (46,47). However, supplementation with 15% of inulin in syngeneic wild type mice transplanted with tumors cells subcutaneously presented a slower tumor growth rate (48), and supplementation with 10% GOS in rats receiving azoxymethane and dextran sodium sulfate to induce CRC inhibited tumor growth in the colon (49). These studies did not assess the possible presence of pks + E. coli strains, which may modify responses to oligosaccharides in the tested CRC models.…”
Section: Discussionmentioning
confidence: 99%
“…Development of the research of gut microbiome involves not only the drug and TCM but also the daily diet of humans. Recently, a rapidly increasing number of studies have indicated the crucial role of the diet for the treatment of disease (Leboeuf et al, 2020;Li et al, 2020b;Moayyedi et al, 2020;Naudin et al, 2020;Yu et al, 2020). In addition, studies about the close relationship between the diet and the intestinal flora have gradually aroused attention, which may offer us some new perspective for disease prevention.…”
Section: Close Relationships Among Diet Gut Microbiome and Health Carementioning
confidence: 99%
“…[ 90 ] and Akkermansia muciniphila [ 91 , 92 ], which are involved in inhibiting melanoma growth [ 93 ]. Addition of inulin and mucin to the diet induces anti-tumor immune responses and inhibits subcutaneously implanted BRAF mutant melanoma in a syngeneic mouse model [ 94 ]. There is a growing body of evidence that microbiome enhances the effectiveness of chemotherapy, radiotherapy and immunotherapy [ 95 , 96 ].…”
Section: Perspectivesmentioning
confidence: 99%